A STUDY ON THE USE OF CAPTIONED NEWS VIDEO TO IMPROVE EFL STUDENTS’ LISTENING SKILL - Cynthia; Nihta Liando; Rinny Rorimpandey (Program Studi Pendidikan Bahasa Inggris, 2023)
The aim of this research was to examine whether the use of captioned news video improve EFL students’ listening skill or not. The research was conducted at SMAN 1 Guru Lombok Kalawat, North Minahasa, North Sulawesi, Indonesia. The subject of the research were twenty-eight students at grade ten-one. The research used test as the instrument to collecting the numeric data. The test consisted of four sections. Each section has five number in different form: true-false, multiple choice, matching, and fill in the blank. The research method was quantitative pre-experimental one group pre-test and post-test. The treatment given was a captioned news video. The findings were the use of captioned news video improved EFL students’ listening skill. It was shown in the comparison of the mean score of pre-test and post-test. Before the treatment the mean score was 33,75 then after the treatment the mean score got increased became 78,75. It is proved that the treatment was working to the subjects of this research.